Concomitant and hybrid therapy for Helicobacter pylori infection: A randomized clinical trial. Issue 9 (September 2015) - Heo, Jun; Jeon, Seong Woo; Jung, Jin Tae; Kwon, Joong Goo; Lee, Dong Wook; Kim, Hyun Soo; Yang, Chang Hun; Park, Jeong Bae; Park, Kyung Sik; Cho, Kwang Bum; Lee, Si Hyung; Jang, Byung Ik; et al.
Abstract Background and Aims This study aimed to validate the equivalence of first‐line concomitant and hybrid regimens for Helicobacter pylori infection in an era of increasing antibiotic resistance. The study also aimed to assess regimen compliance. Methods H . pylori‐infected patients from six hospitals in Korea were randomly assigned to either concomitant or hybrid regimens. The concomitant regimen consisted of 20 mg of esomeprazole, 1 g of amoxicillin, 500 mg of clarithromycin, and 500 mg metronidazole, twice daily for 10 days. The hybrid regimen consisted of a 5‐day dual therapy (20 mg of esomeprazole and 1 g of amoxicillin, twice daily) followed by a 5‐day quadruple therapy (20 mg of esomeprazole, 1 g of amoxicillin, 500 mg of clarithromycin, and 500 mg of metronidazole, twice daily). Results Eradication rates for concomitant and hybrid therapy were 78.6% (187/238) and 78.8% (190/241) in the intention‐to‐treat analysis, and 89.8% (176/196) and 89.6% (181/202) in the per protocol analysis. For both analyses, 95% confidence intervals fell within the ± 8% equivalence margin. Adherence was better in the hybrid group (95.0%) than in the concomitant group (90.1%), a difference that was borderline significant (P = 0.051). Adverse event rates were higher in the concomitant group than in the hybrid group for nausea (15.8% vs 8.8%; P = 0.028) and regurgitation (17.6% vs 10.7%; P = 0.040). Conclusion As compared with concomitant therapy, hybrid therapy offered similar efficacy, better compliance, and fewer adverse events. Hybrid therapy could be a reasonable first‐line treatment option for H. pylori in areas with high antibiotics resistance.